2019
DOI: 10.1002/mabi.201900226
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Sustained BMP Delivery in the Prevention of Medication‐Related Osteonecrosis of the Jaw (MRONJ) in a Rat Model

Abstract: Medication‐related osteonecrosis of the jaw (MRONJ) poses an ongoing challenge for clinicians and researchers. Currently, there is a lack of preventative measures available for at‐risk patients undergoing tooth extractions, especially those with prior bisphosphonate treatment due to osteoporosis or bone metastasis diagnoses. Here, these issues are addressed using a preventative tissue engineering strategy against MRONJ development. This study evaluates the efficacy of a poly(ethylene glycol)‐heparin hydrogel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…However, the bone regeneration rate promoted by BMP-2/hydrogel was moderate, i.e., the bone volume/total volume in the tooth extraction sockets in the BMP-2/hydrogel group (69.1% ± 13.1%) increased only 1.36 times compared to the non-transplantation group (50.9% ± 8.8%). Moreover, a detailed analysis of necrotic bone with empty lacunae, which is one of the important parameters used to assess the severity of MRONJ, was not performed [ 22 ]. Jung et al have reported a clinical preliminary study showing that only transplantation of BMP-2 absorbed with a collagen sponge (BMP-2/collagen) could not significantly induce bone formation at the MRONJ site, compared with the non-transplantation group, and that PTH administration would be necessary to stimulate the effect of BMP-2 in inducing bone formation [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the bone regeneration rate promoted by BMP-2/hydrogel was moderate, i.e., the bone volume/total volume in the tooth extraction sockets in the BMP-2/hydrogel group (69.1% ± 13.1%) increased only 1.36 times compared to the non-transplantation group (50.9% ± 8.8%). Moreover, a detailed analysis of necrotic bone with empty lacunae, which is one of the important parameters used to assess the severity of MRONJ, was not performed [ 22 ]. Jung et al have reported a clinical preliminary study showing that only transplantation of BMP-2 absorbed with a collagen sponge (BMP-2/collagen) could not significantly induce bone formation at the MRONJ site, compared with the non-transplantation group, and that PTH administration would be necessary to stimulate the effect of BMP-2 in inducing bone formation [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, BMP-2 has been considered to have only a moderate effect on the prevention or reconstruction of MRONJ-associated symptoms [ 22 ]. Moreover, Jung et al have shown that the combination of parathyroid hormone (PTH) and BMP-2 helped to significantly improve bone formation compared with BMP-2 alone or a control group [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry was carried out on paraffin sections as described previously [ 39 , 40 ]. Briefly, the sections were deparaffinized and rehydrated before they were incubated for 10 min with proteinase K (S302080, Dako, Sydney, Australia) for antigen retrieval.…”
Section: Methodsmentioning
confidence: 99%
“…Although the pathogenesis of MRONJ is not completely understood there are hypothesizes which suggest that MRONJ is related in remodeling and healing of the jaws. Mechanisms that frequently mentioned are inhibition of osteoclast differentiation, inhibition of angiogenesis, induced apoptosis of osteoclasts, reduction of bone turnover (Ristow et al, 2015;Berg et al, 2016;Brierly et al, 2019). Oral malodor, erythema, soft tissue ulceration, which is persisted for more than 8 weeks, neuropathy, jaw pain, mucosal swelling, trismus, exposed bone or a non-healing extraction socket, paresthesia and suppuration are the common clinical signs and symptoms of MRONJ (Brierly et Five different hypotheses were suggested for the pathophysiology of the MRONJ since the first osteonecrosis of the jaws cases were reported; however, the exact pathophysiology is not determined yet (Marx, 2003;Aghaloo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%